Temporal and spatial dynamics of ischemic stroke lesions after acute therapy: a comprehensive edema assessment using combined 1H- and 23Na-MRI : imaging - Mohamed, Sherif A.; Adlung, Anne; Ludwig, Nadia K.; Samartzi, Melina; Schad, Lothar R.; Fatar, Marc; Neumaier-Probst, Eva (Cerebrovascular diseases, 2025)
Introduction: Ischemic cerebral stroke initiates a complex cascade of pathophysiological events, involving various forms of molecular shifts and edema. Early intervention is pivotal in minimizing tissue loss and improving clinical outcomes. This study explores the temporal and spatial evolution of tissue sodium concentration (TSC) in acute ischemic lesions after acute therapy using 23Na-MRI in addition to conventional 1H-MRI. Methods: Prospectively, from examined 58 patients with acute ischemic stroke with a combined 1H/23Na-MRI within 72 h of symptom onset after receiving acute therapy, 31 patients were included in the evaluation of this study. After co-registration of the 23Na-MRI images to the morphological 1H-MRI images, manual segmentation of the ischemic lesions was performed, and the ADC and TSC measurements were quantified and correlated with the time of onset and lesion volume. Results: The mean TSC in ischemic lesions correlated positively with lesion volume (r = 0.52, p = 0.002) and showed a significant association with the time of stroke onset (r = 0.8, p < 0.001). Patients who were treated only with intravenous rtPA showed homogenous sodium signal intensity in the ischemic lesions, whereas the patients who received mechanical recanalization exhibited distinctive sodium signal intensity patterns with focal significant TSC differences. Conclusion: The integration of 1H- and 23Na-MRI provides a nuanced understanding of temporal and spatial changes due to different types of edema in ischemic stroke lesions following acute treatment. Further exploration of these findings may enhance our understanding of stroke pathophysiology and guide personalized therapeutic interventions.